Recruitment of TikTok Live Hosts for Selling Clothes Using the MOORA Method - Sedihati Kayan Lumbangaol; Nasib Marbun (CV. Media Digital Publikasi Indonesia, 2023)
Mistakes in recruiting Hosts for the business of selling clothes on TikTok live streaming can have a negative impact on business owners, because Host failure can cause the products offered not to sell to potential customers. To overcome this problem, a decision support system is needed as a support tool for clothing selling entrepreneurs in recruiting TikTok Live Hosts that are relevant and can contribute to the development of their business. In this study the authors used Multi-Objective Optimization on the Basis of Ratio Analysis (MOORA) for the TikTok Live Host recruitment process with 5 (five) alternatives and 5 assessment criteria in subjective decision making. The results of this study indicate that the alternative that gets the first ranking position and is recommended to be accepted as a TikTok Live Host is A5 (Rina) with a value of 0.2752. As for the ranking order of other alternatives, namely A1 (Janses) with a value of 0.2738 at rank 2, A3 (Aisyah) with a value of 0.2582 at rank 3, A4 (Kylen) with a value of 0.2460 at rank 4, and A2 (Delima) with a value of 0.2190 at rank 5.